Cytotoxic innate intraepithelial lymphocytes control early stages of Cryptosporidium infection - Hariss, Fatima; Delbeke, Marie; Guyot, Karine; Zarnitzky, Pauline; Ezzedine, Mohamad; Certad, Gabriela; Meresse, Bertrand (Frontiers in Immunology, 2023)
Background Intraepithelial lymphocytes (IELs) are the first immune cells to contact and fight intestinal pathogens such as Cryptosporidium, a widespread parasite which infects the gut epithelium. IFN-γ producing CD4+ T IELs provide an efficient and a long-term protection against cryptosporidiosis while intraepithelial type 1 innate lymphoid cells limits pathogen spreading during early stages of infection in immunodeficient individuals. Yet, the role of T-cell like innate IELs, the most frequent subset of innate lymphocytes in the gut, remains unknown. Methods To better define functions of innate IELs in cryptosporidiosis, we developed a co-culture model with innate IELs isolated from Rag2-/- mice and 3D intestinal organoids infected with C. parvum using microinjection. Results Thanks to this original model, we demonstrated that innate IELs control parasite proliferation. We further showed that although innate IELs secrete IFN-γ in response to C. parvum, the cytokine was not sufficient to inhibit parasite proliferation at early stages of the infection. The rapid protective effect of innate IELs was in fact mediated by a cytotoxic, granzyme-dependent mechanism. Moreover, transcriptomic analysis of the Cryptosporidium-infected organoids revealed that epithelial cells down regulated Serpinb9b, a granzyme inhibitor, which may increase their sensitivity to cytolytic attack by innate IELs. Conclusion Based on these data we conclude that innate IELs, most likely T-cell-like innate IELs, provide a rapid protection against C. parvum infection through a perforin/granzymes-dependent mechanism. C. parvum infection. The infection may also increase the sensitivity of intestinal epithelial cells to the innate IEL-mediated cytotoxic attack by decreasing the expression of Serpin genes.